Три новых граффити из Херсонеса и ближайшей округи - Туровский, Е.Я. (My University, 1997)
Turovsky E. A. Three New Graffiti from Chersonesus and It's Nearest Area The first of the number of graffiti being presented here is scratched on the bottom of the II cent. B. C. black glaze serving-bowl. That's a dedication to Asklepios. The second one is fulfilled on a clay loom-weight, it includes word «Phaso» (a woman's name). The last graffiti from this batch was possibly ostraka. It is scratched an amphora's sherd; the inscription contains the name and the father name of that person who was put down with the ostrakismos, namely: Kalliad son Syriskos.